2017
DOI: 10.18632/oncotarget.14764
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of endoplasmic reticulum stress response in immune dysfunction of dendritic cells after severe thermal injury in mice

Abstract: Suppressed adaptive immune function is one of the major concerns responsible for the development of opportunistic infections and subsequent sepsis with high mortality in severe burns. Endoplasmic reticulum stress (ERS) is the endogenous self-protective mechanism, and it plays an important role in almost every process of living by regulating the balance between homeostasis and apoptosis. The current study investigated the involvement of ERS in the pathogenesis of dysfunction of dendritic cells (DCs) in burn mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…HMGB1, one of the key damage-associated molecular patterns, is an important late-acting inflammatory cytokine of sepsis that can be actively secreted by immune cells or passively released by injured or necrotic cells. It has been documented that HMGB1 is critically involved in host immune dysfunction and various diseases [30][31][32] , and it acts as a potent mediator of DC activation, maturation as well as survival [13][14][15][33][34][35] . In the present study, we investigated the proapoptotic effect of HMGB1 stimulation on DC2.4 cells in vitro, showing a time-dependent and dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HMGB1, one of the key damage-associated molecular patterns, is an important late-acting inflammatory cytokine of sepsis that can be actively secreted by immune cells or passively released by injured or necrotic cells. It has been documented that HMGB1 is critically involved in host immune dysfunction and various diseases [30][31][32] , and it acts as a potent mediator of DC activation, maturation as well as survival [13][14][15][33][34][35] . In the present study, we investigated the proapoptotic effect of HMGB1 stimulation on DC2.4 cells in vitro, showing a time-dependent and dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies proved that the overwhelming ERS response in splenic DCs in severe thermal injuries could be the main cause to initiate excessive apoptosis and dysfunction of DCs, thereby resulting in immunosuppression and even death [13][14][15] . The pathophysiological mechanism is highly related to an important late-acting cytokine high mobility group box-1 protein (HMGB1), which is increased markedly in sepsis and plays an important role in provoking inflammation and immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…These changes indicate that the stimulation of IRE1-XBP1 signaling switched the immunosuppressive phenotype of DCs and thus enhanced tumor progression. The ER stress-induced suppression of DCs has also been observed after a severe thermal injury in mice [147]. Zhu et al [147] reported that a burn injury promoted the appearance of ER stress in splenic DCs which reduced the maturation of these cells and increased their apoptosis.…”
Section: Er Stress Augments the Immunosuppressive Phenotype Of Immunementioning
confidence: 96%
“…The ER stress-induced suppression of DCs has also been observed after a severe thermal injury in mice [147]. Zhu et al [147] reported that a burn injury promoted the appearance of ER stress in splenic DCs which reduced the maturation of these cells and increased their apoptosis. The splenic DCs from injured mice also displayed a reduced capacity to enhance T cell proliferation and Th1 polarization.…”
Section: Er Stress Augments the Immunosuppressive Phenotype Of Immunementioning
confidence: 96%
“…Histological, immunological and biochemical manifestations of adenohypophysis [2], adrenal glands [10,18] and thymus [13,28] damages have been established at different times in the course of burn disease, which lead to severe organ damage [23,22]. However, the molecular mechanisms of these disorders remain poorly understood, which makes it difficult to develop pathogenetic treatments for burn disease.…”
mentioning
confidence: 99%